Hetero Diels–Alder Reaction and Ene Reaction of Acylnitroso Species in situ Generated by Hypoiodite Catalysis; European Journal of Organic Chemistry; Vol. 2018, iss. 45 - Uraoka S. Saki; Shinohara I. Ikumi; Shimizu H. Hisato; Noguchi K. Keiichi; Yoshimura A. Akira; Zhdankin V. V. Viktor Vladimirovich; Saito A. Akio (2018, 2018)
Title screen